2022
DOI: 10.15585/mmwr.su7103a4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Racism and Demographic, Mental Health, and Behavioral Characteristics Among High School Students During the COVID-19 Pandemic — Adolescent Behaviors and Experiences Survey, United States, January–June 2021

Abstract: Perceived racism in school (i.e., a student’s report of being treated badly or unfairly because of their race or ethnicity) is an important yet understudied determinant of adolescent health and well-being. Knowing how perceived racism influences adolescent health can help reduce health inequities. CDC’s 2021 Adolescent Behaviors and Experiences Survey (ABES), an online survey of a probability-based, nationally representative sample of U.S. public- and private-school students in grades 9–12 (N = 7,705), was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
(22 reference statements)
3
40
2
Order By: Relevance
“…Our study also suggests that young adults who self-reported experiences of ethno-racial discrimination were less likely to access mental health services. This finding is particularly concerning given that young adults who experienced ethno-racial discrimination during the pandemic have higher risks of reporting negative mental health outcomes, including poor mental health, psychological distress and depression (Hahm et al, 2021 ; Mpofu et al, 2022 ; Oh et al, 2021 ). A systematic review also indicated that the COVID-19 pandemic contributed to increased ethno-racial discrimination in high-income countries, including in social spaces, school/work or within clinical settings (Yashadhana et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also suggests that young adults who self-reported experiences of ethno-racial discrimination were less likely to access mental health services. This finding is particularly concerning given that young adults who experienced ethno-racial discrimination during the pandemic have higher risks of reporting negative mental health outcomes, including poor mental health, psychological distress and depression (Hahm et al, 2021 ; Mpofu et al, 2022 ; Oh et al, 2021 ). A systematic review also indicated that the COVID-19 pandemic contributed to increased ethno-racial discrimination in high-income countries, including in social spaces, school/work or within clinical settings (Yashadhana et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Now more than ever, stigmatized youth (i.e., children, adolescents, and young adults with one or more stigmatized identities; e.g., youth of Color, girls, transgender youth) are in need of effective mental health treatment. Inequities in mental health problem severity, diagnosis, and treatment between stigmatized and privileged groups (e.g., youth of Color vs. White youth, lesbian, gay, bisexual, or other sexual minority vs. heterosexual youth) are longstanding (Alegria et al, 2010;Bui & Takeuchi, 1992;Connolly et al, 2016;Garland et al, 2005;Rodgers et al, 2021;Russell & Fish, 2016), and these gaps are widening in the ongoing pandemic (Banks, 2021;Benton et al, 2022;Bhogal et al, 2021;Fish et al, 2020;Hawke et al, 2021;Mpofu, 2022;Penner et al, 2021;Rothe et al, 2021;Saunders et al, 2021). These inequities are primarily attributable to these youth's experiences of stigma at multiple levels: (1) internalized stigma (i.e., self-stigma), or one's adoption of stigma-related beliefs resulting from exposure to stigmatizing environments or relationships (e.g., a girl believing that being assaulted was because of her physical attractiveness; Moses, 2009), (2) interpersonal stigma, which stigmatized individuals experience in interpersonal interactions (e.g., a peer saying "no homo;" sexual violence against girls; Fish, 2020;Jones & Neblett, 2017); and (3) structural stigma, or laws/policies (e.g., a state policy prohibiting gender-affirming care for transgender youth) and norms/attitudes (e.g., the belief that Black people will bring violence into neighborhoods they move into; Krieger et al, 2010) that negatively impact stigmatized people (Alvarez et al, 2021;Beccia et al, 2022;Castro-Ramirez et al, 2021;Hatzenbuehler, 2017).…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%
“…Now more than ever, stigmatized youth (i.e., children, adolescents, and young adults with one or more stigmatized identities; e.g., youth of Color, girls, transgender youth) are in need of effective mental health treatment. Inequities in mental health problem severity, diagnosis, and treatment between stigmatized and privileged groups (e.g., youth of Color vs. White youth, lesbian, gay, bisexual, or other sexual minority vs. heterosexual youth) are longstanding (Alegria et al, 2010;Bui & Takeuchi, 1992;Connolly et al, 2016;Garland et al, 2005;Rodgers et al, 2021;Russell & Fish, 2016), and these gaps are widening in the ongoing pandemic (Banks, 2021;Benton et al, 2022;Bhogal et al, 2021;Fish et al, 2020;Hawke et al, 2021;Mpofu, 2022;Penner et al, 2021;Rothe et al, 2021;Saunders et al, 2021). These inequities are primarily attributable to these youth's experiences of stigma at multiple levels: (1) internalized stigma (i.e., self-stigma), or one's adoption of stigma-related beliefs resulting from exposure to stigmatizing environments or relationships (e.g., a girl believing that being assaulted was because of her physical attractiveness; Moses, 2009), (2) interpersonal stigma, which stigmatized individuals experience in interpersonal interactions (e.g., a peer saying "no homo;" sexual violence against girls; Fish, 2020;Jones & Neblett, 2017); and (3) structural stigma, or laws/policies (e.g., a state policy prohibiting gender-affirming care for transgender youth) and norms/attitudes (e.g., the belief that Black people will bring violence into neighborhoods they move into; (e.g., the belief that Black people will bring violence into neighborhoods they move into; Krieger et al, 2010) that negatively impact stigmatized people (Alvarez et al, 2021;Beccia et al, 2022;Castro-Ramirez et al, 2021;Hatzenbuehler, 2017).…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%